Peran Guru Pendidikan Agama Islam dalam Meningkatkan Perilaku Islami Siswa di SD Negeri 01 Indralaya - Almujahid, Cittra Juniarni; Abdallah, Abdallah; Helyani, Helyani (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
Islamic Religious Education teachers are expected to be able to teach, guide, and provide good examples to students on how to behave properly. The role of Islamic Religious Education teachers has a central position in shaping student behavior in schools, if teachers are able to direct students to behave Islamically, it is not impossible in the school to create a culture of Islamic behavior. This research uses descriptive qualitative research. The data obtained are in the form of primary and secondary data. The data analysis used is data reduction, data presentation and conclusion drawing as the final result of this research. The research results obtained are as follows: First, namely the Role of Islamic Religious Education Teachers in Improving Students' Islamic Behavior at SD Negeri 01 Indralaya including: a. using the lecture method and the habituation method, b. maximize religious facilities in schools, c. Cultivate 5S, d. always try to set a good example or role model for students. Second, the supporting factors of Islamic religious education teachers in improving the Islamic behavior of students at SD Negeri 01 Indralaya are: a. there is cooperation between teachers; b. the participation of parents of students; c. sanctions for students who violate. While the inhibiting factors are: a. the absence of a prayer room so that the process of forming Islamic behavior is hampered; b. lack of books on Islamic studies